Renin-angiotensin system inhibition after surgical aortic valve replacement for aortic stenosis - Martinsson Andreas; Törngren Charlotta; Nielsen Susanne J; Pan Emily; Hansson Emma C; Taha Amar; Jeppsson Anders (BMJ PUBLISHING GROUP, 2025)
Objective
The optimal medical therapy after surgical aortic valve replacement (SAVR) for aortic stenosis remains unknown. Renin-angiotensin system (RAS) inhibitors could potentially improve cardiac remodelling and clinical outcomes after SAVR.
Methods
All patients undergoing SAVR due to aortic stenosis in Sweden 2006-2020 and surviving 6 months after surgery were included. The primary outcome was major adverse cardiovascular events (MACEs; all-cause mortality, stroke or myocardial infarction). Secondary endpoints included the individual components of MACE and cardiovascular mortality. Time-updated adjusted Cox regression models were used to compare patients with and without RAS inhibitors. Subgroup analyses were performed, as well as a comparison between angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs).
Results
A total of 11 894 patients (mean age, 69.5 years, 40.4% women) were included. Median follow-up time was 5.4 (2.7-8.5) years. At baseline, 53.6% of patients were dispensed RAS inhibitors, this proportion remained stable during follow-up. RAS inhibition was associated with a lower risk of MACE (adjusted hazard ratio (aHR) 0.87 (95% CI 0.81 to 0.93), p<0.001), mainly driven by a lower risk of all-cause death (aHR 0.79 (0.73 to 0.86), p<0.001). The lower MACE risk was consistent in all subgroups except for those with mechanical prostheses (aHR 1.07 (0.84 to 1.37), p for interaction=0.040). Both treatment with ACE inhibitors (aHR 0.89 (95% CI 0.82 to 0.97)) and ARBs (0.87 (0.81 to 0.93)) were associated with lower risk of MACE.
Conclusion
The results of this study suggest that medical therapy with an RAS inhibitor after SAVR is associated with a 13% lower risk of MACE and a 21% lower risk of all-cause death.